2016
DOI: 10.1007/s00467-016-3433-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acute kidney injury in children worldwide, including developing countries

Abstract: In this review we summarize the world-wide epidemiology of acute kidney injury (AKI) in children with special emphasis on low-income countries, notably those of the sub-Saharan continent. We discuss definitions and classification systems used in pediatric AKI literature. At present, despite some shortcomings, traditional Pediatric Risk Injury Failure Loss and End Stage Kidney Disease (pRIFLE) and Kidney Disease Improving Global Outcomes (KDIGO) systems are the most clinically useful. Alternative definitions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 115 publications
(144 reference statements)
0
38
0
4
Order By: Relevance
“…Overall mortality rate was 26.9%, but of the 59 dead patients, 11 died after recovery from AKI. Median time for mortality was 8 days (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Overall patient survival rates were 83.6% for 10 days and 47.3% for 28 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall mortality rate was 26.9%, but of the 59 dead patients, 11 died after recovery from AKI. Median time for mortality was 8 days (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Overall patient survival rates were 83.6% for 10 days and 47.3% for 28 days.…”
Section: Resultsmentioning
confidence: 99%
“…Postcardiac surgery, sepsis, multiorgan failure, haemato‐oncological diseases, trauma, and exposure to nephrotoxic agents are the main causes of AKI in the critically ill child, while in the hospitalized non‐critically ill child, exposure to nephrotoxins is a major cause of AKI . Studies on community‐acquired AKI in children remain scarce and are generally based on registries of in hospital populations …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The AKI‐EPI study, an international cross‐sectional study performed at 97 centers in patients during their first week of ICU admission, showed that 57% of critically ill patients developed AKI . Likewise, the major relevance of AKI among severely ill pediatric patients is also evident, with an AKI prevalence of 25% in this group …”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…50 Likewise, the major relevance of AKI among severely ill pediatric patients is also evident, with an AKI prevalence of 25% in this group. 51,52 A serious problem among ICU and PICU patients, AKI, is also frequently present in potential DDs. The kidney has an intrinsic capacity to repair itself and recover from an ischemic or toxic insult, 53 and the majority patients with AKI may fully recover their renal function.…”
Section: Acute K Idne Y Inj Urymentioning
confidence: 99%